First Place: A prospective, randomized controlled trial of the impact of written discharge instructions for postoperative opioids on patient pain satisfaction and on minimizing opioid risk exposure in orthopaedic surgery. Issue 4 (July 2018) - Singh, Supriya; Clarke, Collin; Lawendy, Abdel Rehman; Macleod, Mark; Sanders, David; Tieszer, Christina
Abstract : Background: Prescription opioid misuse is a significant issue with multiple consequences for our patients and society. The purpose of this study was to evaluate the role of a postoperative pain guideline pamphlet on patient pain satisfaction, on number of patients seeking a renewal prescription, and on appropriate disposal of leftover prescription medication. Methods: This prospective, randomized controlled trial included patients aged 18 to 65 yr undergoing elective foot and ankle surgery, who were opioid naïve and had no preexisting chronic pain conditions. Patients consenting to participate were divided into low-, medium-, and high-use groups according to anticipated postoperative prescription narcotic usage. Patients in each group were randomized to the control group that received no written discharge instructions, or the intervention group that received written instructions outlining postoperative pain expectations and recommendations for opioid medication usage and disposal. Both groups received equivalent prescriptions targeted to the use group (low, medium, or high). At the 4-week postoperative mark, a telephone interview was conducted to evaluate the primary outcome of pain satisfaction using a modified brief pain inventory. Secondary outcomes included renewal of opioid prescription and disposal method of leftover medication. Results: A total of 80 patients were recruited for this study. Of the 80 patients, 22 were classified as low use, 45 moderate use, and 13 high use. There was no difference among group demographics, other than the surgery being performed. Of the 80 patients, 41 received postoperative pain instructions and 39 did not. On average, pain satisfaction postoperatively was 8.19/10, where 10/10 represented completely satisfied. Interference scores averaged 27.18/70. Interestingly, only seven patients (six moderate use and one high use) used the entirety of their prescription, and only five patients required a renewal of their prescription. Only five patients returned their surplus medication to the pharmacy despite 41 patients receiving direct instructions to do so. Conclusions: Written discharge instructions in this patient population did not appear to improve postoperative pain scores. Interestingly, this study captured that a small percentage of postoperative pain medication prescriptions are completely utilized. Even more concerning is the fact that very little of the leftover pain medication is disposed of appropriately. Overprescribing narcotic medication may contribute to the issue of opioid abuse, and we should consider our role in minimizing opioid prescriptions postoperatively. Abstract : Supplemental Digital Content is available in the text.